2016
DOI: 10.1002/2015jg003061
|View full text |Cite
|
Sign up to set email alerts
|

Effects of permafrost aggradation on peat properties as determined from a pan‐Arctic synthesis of plant macrofossils

Abstract: 37Permafrost dynamics play an important role in high-latitude peatland carbon balance and are key 38 to understanding the future response of soil carbon stocks. Permafrost aggradation can control 39 the magnitude of the carbon feedback in peatlands through effects on peat properties. We 40 compiled peatland plant macrofossil records for the northern permafrost zone (515 cores from 41 280 sites) and classified samples by vegetation type and environmental class (fen, bog, tundra 42 and boreal permafrost, thawed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
121
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(145 citation statements)
references
References 106 publications
(215 reference statements)
14
121
1
Order By: Relevance
“…Treat et al () compiled a database of 273 peat samples from the permafrost tundra zone and found mean values of peat C content of 39.5 ± 9.0%, C:N ratios of 34 ± 18, and a DBD of 0.16 ± 0.21 g cm −3 , in the range of our mean values for the 10 peat samples from Abisko (Figure ).…”
Section: Discussionsupporting
confidence: 66%
“…Treat et al () compiled a database of 273 peat samples from the permafrost tundra zone and found mean values of peat C content of 39.5 ± 9.0%, C:N ratios of 34 ± 18, and a DBD of 0.16 ± 0.21 g cm −3 , in the range of our mean values for the 10 peat samples from Abisko (Figure ).…”
Section: Discussionsupporting
confidence: 66%
“…In the bottom part of both peat sequences the main peat‐forming plants included Cyperaceae (Figure , phase A; Figure , phases A and B). The presence of Carex fruits and rootlets, as well as brown mosses in both sites indicates that during this period the peatlands operated as fens, a widespread wetland type in the permafrost area of the northern hemisphere (Vardy et al , ; Kuhry, ; Teltewskoi et al , ; Treat et al , ). Pollen data indicate that between 2650 and 2300 cal yr BP the non‐peatland community at Marooned was dominated by Betula .…”
Section: Discussionmentioning
confidence: 93%
“…Within a radius of 350 m around the landscaper tower, 21% of the land surface was classified as transition zone. Due to their differing hydrology, vegetation composition, and nutrient availability, CO 2 flux dynamics of fens most likely differ from CO 2 flux dynamics of collapse-scar bogs (e.g., Bubier, 1995;Yu, 2006;Treat et al, 2016). Transition zones are part of the wetland land cover type and their definition is to some extent arbitrary, as a reference year (here 1977, the first year of available aerial photography) is used to differentiate between gradual transition zones and interior wetlands.…”
Section: Eddy Covariance Measurementsmentioning
confidence: 99%
“…In contrast to changes in T a and precipitation, SW in is more strongly bound to latitude. A shift from permafrost peatland landscapes with large organic C stocks [mean of 106 kg m À2 AE45 (AEone standard deviation) for forested permafrost plateaus (n = 158); 117 kg m À2 AE 65 for collapse-scar bogs (n = 52); data from Treat et al, 2016] to landscapes with low C stocks would result in large net CO 2 emissions. S6) is therefore likely to increase ER more than GPP, particularly for the RCP8.5 scenario (Fig.…”
Section: Direct Climate Change Impacts On Carbon Dioxide Fluxesmentioning
confidence: 99%
See 1 more Smart Citation